RUMAH BIMBINGAN USAHA KECIL DAN MENENGAH DALAM PENGEMBANGAN KREATIVITAS PENGELOLAAN KEUANGAN MELALUI COMIC STRIP CREATOR - Agustyawati, Dwi; Hasni, Hasni; Katjinah, Husnah; Rais.R, Muhammad; Zarliani Uli, Nur; Hamsir, Mega (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service program aims to enhance the creativity of Small and Medium Enterprises (SMEs) in financial management through the use of Comic Strip Creator media. The program was conducted in Betoambari District, Baubau City, targeting SME actors who need to improve their skills in recording and managing finances in a creative and engaging way. The method included interactive training, technical mentoring, and hands-on practice in creating comic strips that illustrate business financial situations. The results indicate that participants gained a better understanding of the importance of systematic financial recording and learned to communicate financial concepts visually. This creative approach successfully motivated SMEs actors to adopt more disciplined and communicative financial management practices in their businesses